The Role of Class Reading Corners in Improving Student Literacy in PLP Activities at SDK Majamere - Pasu, Maria Lidvina; Kua, Maria Yuliana (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2024)
The school literacy movement program is defined as the ability to access, understand, and utilize something intelligently through various activities, such as writing, reading, and listening. The class reading corner also functions as a mini library to help students become more familiar with and familiar with reading books. Based on the results of observations on the implementation of PLP II, it was found that students were less interested in reading, the AKM results showed a literacy Pre-Test score of 42%. The use of class reading corners to increase students' interest in reading is the purpose of this study. This study uses descriptive qualitative research using test, observation, and interview methods. Data collection techniques through tests. The instruments are in the form of AKM Pre-Test and Post-Test sheets. The subjects of this research are 19 students consisting of 9 female students and 10 male students in class V SDK Majamere. The results of the AKM Post-Test activities increased by 47%, with the results of the Post Test literacy percentage of 89%, this is due to the creation of a class reading corner. Based on the researcher's findings, the positive impact of the literacy movement on the reading interest of fifth grade students increased after the creation of a class reading corner.